2008
DOI: 10.2967/jnumed.107.047548
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Serial Cardiac 123I-MIBG Imaging in Patients with Stabilized Chronic Heart Failure and Reduced Left Ventricular Ejection Fraction

Abstract: Many studies have shown that a one-time 123 I-metaiodobenzylguanidine ( 123 I-MIBG) scintigraphic study during a stable period is useful for determining the prognosis of patients with chronic heart failure (CHF). However, the findings from this imaging modality are well known to be improved by medical treatment for heart failure. Accordingly, this study was performed to determine whether serial 123 I-MIBG scintigraphic studies represent a reliable prognostic marker for patients with CHF. Methods: A total of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 36 publications
2
103
0
Order By: Relevance
“…Increased sympathetic nervous activity or denervation are seen in heart failure patients, and could be imaged with myocardial 123 I-MIBG image (16). Several reports have shown the clinical usefulness of 123 I-MIBG for prediction of major cardiac events, including heart failure hospitalization or cardiac death (17)(18)(19)(20), discharge of implantable cardioverter defibrillator (21), or evaluation of the effectiveness of betablockade (22)(23)(24)(25)(26), renin-angiotensin-aldosterone system inhibitor (27)(28)(29), and nicorandil (30,31) in patients with heart failure. And, a multi-center study of ADMIRE-HF (AdreView Myocardial Imaging for Risk Evaluation in Heart Failure) trial was conducted (32), and meta-analysis of Japanese-single cohort was also performed (33) and verified the perceptions of the previous studies.…”
Section: Sympathetic Nerve Functional Imaging With 123 I-mibgmentioning
confidence: 99%
“…Increased sympathetic nervous activity or denervation are seen in heart failure patients, and could be imaged with myocardial 123 I-MIBG image (16). Several reports have shown the clinical usefulness of 123 I-MIBG for prediction of major cardiac events, including heart failure hospitalization or cardiac death (17)(18)(19)(20), discharge of implantable cardioverter defibrillator (21), or evaluation of the effectiveness of betablockade (22)(23)(24)(25)(26), renin-angiotensin-aldosterone system inhibitor (27)(28)(29), and nicorandil (30,31) in patients with heart failure. And, a multi-center study of ADMIRE-HF (AdreView Myocardial Imaging for Risk Evaluation in Heart Failure) trial was conducted (32), and meta-analysis of Japanese-single cohort was also performed (33) and verified the perceptions of the previous studies.…”
Section: Sympathetic Nerve Functional Imaging With 123 I-mibgmentioning
confidence: 99%
“…As interpretation of planar images requires analysis of the upper mediastinum, there is concern that smaller field of view cardiac cameras, or performing SPECT imaging alone, would not be suitable for cardiac 123 ImIBG imaging. However, a recent study by Chen et al 47 reported development of a technique to derive satisfactory quantitative parameters for SPECT imaging limited to the cardiac field…”
Section: Imaging Techniquementioning
confidence: 99%
“…Most clinical and published work use a low energy high-resolution (LEHR) collimator, although slight differences among collimators in different countries (US vs Europe vs Japan) yield slightly different normal quantitative values. However, because of septal penetration by higher energy ([400 keV) 123 I photons, mostly a 529-keV emission, some have recommended using a medium energy collimator that has been shown to provide superior quantitative accuracy. 36,43,44 To compensate for the resulting corruption of image quantitation related to LEHR collimator penetration by higher energy photons, Chen et al 45,46 have developed a mathematical technique (iterative reconstruction with deconvolution of septal penetration) that appears to improve quantitative accuracy of cardiac 123 I-mIBG uptake in reference to a phantom standard.…”
Section: Imaging Techniquementioning
confidence: 99%
See 2 more Smart Citations